Investigating the molecular mechanisms of the “Astragalus-Codonopsis” herb pair in treating diabetes: a network pharmacology and bioinformatics approach with molecular docking validation - Yang, Jinliang; Li, Mingyang; Zhu, Ziyue; Han, Fengling; Ma, Yanyan; Hou, Jinbo; Zhao, Qingfeng; Yuan, Hui; Li, XiuMei (Frontiers in Bioengineering and Biotechnology, 2025)
Astragalus membranaceus and Codonopsis pilosula are widely used in traditional chinese medicine for the treatment of diabetes because of their notable hypoglycemic pharmacological effects. Studies have indicatedthat the active compounds in the Astragalus-Codonopsis herb pair may exert their hypoglycemic effects through the modulation of the insulin receptor (IRSP) signaling pathway. In this study, the rhamnolitrin and folic acid were confirmed as the key active components in the Astragalus-Codonopsis herb pair that regulate the IRSP, with their synergistic mechanisms in Type 2 Diabetes Mellitus (T2DM) being further systematically explored by network pharmacology combined with DFT theoretical calculation, molecular docking, molecular dynamics simulation and alanine scanning mutation technology. The results suggest that GSK3β is a critical target through which rhamnolitrin and folic acid exert their anti-diabetic effects. Subsequent molecular docking and molecular dynamics simulations confirmed that both active compounds selected in this study can bind stably with the GSK3β protein. Further alanine scanning mutagenesis experiments validated the importance of key amino acid residues in ligand-receptor interactions. Finally, DFT theoretical calculations provided a detailed elucidation of the binding mechanism between the core components (rhamnolitrin and folic acid) and the target protein GSK3β. This study not only revealed the molecular mechanism of Astragalus-Codonopsis for the treatment of type 2 diabetes, provided a theoretical basis for its clinical application, but also provided a potential molecular target for the development of new anti-diabetes drugs.